Recurrence patterns and progression-free survival after chemoradiotherapy with or without consolidation durvalumab for stage III non-small cell lung cancer. (22nd September 2022) - Kishi, Noriko; Matsuo, Yukinori; Shintani, Takashi; Ogura, Masakazu; Mitsuyoshi, Takamasa; Araki, Norio; Fujii, Kota; Okumura, Setsuko; Nakamatsu, Kiyoshi; Kishi, Takahiro; Atsuta, Tomoko; Sakamoto, Takashi; et al.
Abstract: Chemoradiotherapy followed by consolidation durvalumab (CCRT+D) improves survival in patients with stage III non-small-cell lung cancer (NSCLC). We compared recurrence patterns and survival in the CCRT+D and CCRT cohorts. We conducted a multicenter, retrospective study in Japan. Patients who received CCRT for stage III NSCLC were included in this study. Of 178 eligible patients, 136 were in the CCRT+D and 42 were in the CCRT cohorts. Locoregional recurrence (LR), LR plus distant metastases (DM), and DM were observed in 20.6%, 8.8%, 27.9% of the CCRT+D, and 26.2%, 16.7% and 33.3% of the CCRT cohorts, respectively. In-field recurrence was the most common LR pattern in both cohorts. Squamous cell carcinoma and PD-L1 expression < 1%, and female sex and EGFR mutations were significantly associated with an increased risk of LR and DM. In patients with any risk factors for LR, the incidence of LR was similar in the CCRT+D and CCRT (39.5% vs 45.5%). The 24 month progression-free survival (PFS) and overall survival (OS) were 40.3% and 69.4% in the CCRT+D and 24.7% and 61.0% in the CCRT cohorts, respectively. Poor performance status and no consolidation durvalumab were significantly associated with shorter PFS. There was a significant difference in PFS between the CCRT+D and CCRT in the propensity score-matched cohort (HR = 0.51, P = 0.005). In conclusion, consolidation durvalumab decreased both LR and DM, and significantly improved PFS. However, in-field recurrence was still a major problem, as well as DM.